PERANCANGAN DESAIN WEBSITE PROFILE DPKPP MENGGUNAKAN METODE SDLC (SOFTWARE DEVELOPMENT LIFE CYCLE) - Dendy Andra; Yulia Darmi; Tri Puji Astuti; Aprillia Salsabila; Roby Maringga; Afdal Zikri; Alpin Anugerah (CV SWA Anugerah, 2025)
The use of information technology in governance plays a crucial role in enhancing transparency and the efficiency of public services. This study aims to design and develop an official profile website for the Housing, Settlement Areas, and Land Agency (DPKPP) of Bengkulu Province to facilitate the dissemination of information to the public. The website development process employs the System Development Life Cycle (SDLC) methodology, encompassing stages such as needs analysis, system design, implementation, testing, and maintenance. The results indicate that the developed website incorporates key features, including intuitive navigation, a responsive display, and a content management system that simplifies the process for administrators to update information. From a security perspective, role-based authorization and automated backup systems have been implemented to ensure data integrity. This website replaces conventional information distribution methods, which relied heavily on printed media, thereby improving accessibility and communication effectiveness between DPKPP and the public. With the introduction of this platform, information regarding work programs, organizational structure, and official announcements can be communicated more rapidly and extensively. The findings of this study are expected to serve as a reference for other institutions seeking to adopt digital technologies to support a more modern and efficient governance system. Penggunaan teknologi informasi dalam pemerintahan berperan penting dalam meningkatkan transparansi dan efisiensi layanan publik. Penelitian ini bertujuan untuk merancang serta mengembangkan website profil Dinas Perumahan, Kawasan Permukiman, dan Pertanahan (DPKPP) Provinsi Bengkulu guna mempermudah distribusi informasi kepada masyarakat. Proses pengembangan website menerapkan metode System Development Life Cycle (SDLC), yang mencakup tahapan analisis kebutuhan, perancangan, implementasi, pengujian, dan pemeliharaan sistem. Hasil penelitian menunjukkan bahwa website yang dikembangkan memiliki fitur utama seperti navigasi intuitif, tampilan responsif, serta sistem manajemen konten yang memudahkan admin dalam memperbarui informasi. Dari aspek keamanan, diterapkan sistem otorisasi berbasis peran serta pencadangan otomatis untuk menjaga integritas data. Website ini menggantikan metode penyebaran informasi konvensional yang masih bergantung pada media cetak, sehingga meningkatkan aksesibilitas dan efektivitas komunikasi antara DPKPP dan masyarakat. Dengan kehadiran website ini, informasi terkait program kerja, struktur organisasi, serta pengumuman resmi dapat disampaikan secara lebih cepat dan luas. Hasil penelitian ini diharapkan menjadi referensi bagi instansi lain dalam mengadopsi teknologi digital guna mendukung sistem pemerintahan yang lebih modern dan efisien.